The SCITEAS experiment: Optical characterizations of sublimating icy planetary analogues. (May 2015) - Pommerol, A.; Jost, B.; Poch, O.; El-Maarry, M.R.; Vuitel, B.; Thomas, N.
Abstract: We have designed and built a laboratory facility to investigate the spectro-photometric and morphologic properties of different types of ice-bearing planetary surface analogs and follow their evolution upon exposure to a low pressure and low temperature environment. The results obtained with this experiment are used to verify and improve our interpretations of current optical remote-sensing datasets. They also provide valuable information for the development and operation of future optical instruments. The Simulation Chamber for Imaging the Temporal Evolution of Analogue Samples (SCITEAS) is a small thermal vacuum chamber equipped with a variety of ports and feedthroughs that permit both in-situ and remote characterizations as well as interacting with the sample. A large quartz window located directly above the sample is used to observe its surface from outside with a set of visible and near-infrared cameras. The sample holder can be easily and quickly inserted and removed from the chamber and is compatible with the other measurement facilities of the Laboratory for Outflow Studies of Sublimating Materials (LOSSy) at the University of Bern. We report here on the results of two of the first experiments performed in the SCITEAS chamber. In the first experiment, fine-grained water ice mixed with dark organic and mineral matter was left to sublime in vacuum and at low temperature, simulating the evolution of the surface of a comet nucleus approaching the Sun. We observed and characterized the formation and evolution of a crust of refractory organic and mineral matter at the surface of the sample and linked the evolution of its structure and texture to its spectro-photometric properties. In the second experiment, a frozen soil was prepared by freezing a mixture of smectite mineral and water. The sample was then left to sublime for 6 h to simulate the loss of volatiles from icy soil at high latitudes on Mars. Colour images were produced using the definitions of the filters foreseen for the CaSSIS imager of the Exomars/TGO mission in order to prepare future science operations. Highlights: A new facility was developed to study the sublimation of icy analogues. Characterization of the surface texture and spectro-photometric properties. Example of application 1: dust mantle on top of a cometary analogue. Example of application 2: photometry and colour of an icy Martian soil analogue.